Correcting the cut-off point of hemoglobin at high altitude favors misclassification of anemia, erythrocytosis and excessive erythrocytosis - Gonzales, Gustavo F. (2018)
Carta al editor para hacer la corrección del punto de corte de la hemoglobina a gran altitud favorece la clasificación errónea de anemia, eritrocitosis y eritrocitosis excesiva.